2010
DOI: 10.1002/pi.3001
|View full text |Cite
|
Sign up to set email alerts
|

Organic/inorganic support for immobilizing (n‐BuCp)2ZrCl2/TiCl3 hybrid catalyst for use in the preparation of polymer blends

Abstract: Reactor blends of ultrahigh‐molecular‐weight polyethylene (UHMWPE) and low‐molecular‐weight polyethylene (LMWPE) were synthesized by two‐step polymerization using a hybrid catalyst. To prepare the hybrid catalyst, styrene acrylic copolymer (PSA) was first coated onto SiO2/MgCl2‐supported TiCl3; then, (n‐BuCp)2ZrCl2 was immobilized onto the exterior PSA. UHMWPE was produced in the first polymerization stage with the presence of 1‐hexene and modified methylaluminoxane (MMAO), and the LMWPE was prepared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…In addition, the catalytic activity is still promoted, although the pore size and specific surface area are decreased. 31 To recall, the same chemical environment of Ti (See XPS result) and similar TiCl 4 loading in the PS-modified and PS-free catalyst demonstrate the less interaction between PS chains and active species. Thus, this enhanced activity may be attributed to the isolated effect of the inert PS blocks, since the PS phase is thermally immiscible with the polyethylene and serves as the inert isolator for separate the propagated chains.…”
Section: Ethylene Polymerization Resultsmentioning
confidence: 86%
“…In addition, the catalytic activity is still promoted, although the pore size and specific surface area are decreased. 31 To recall, the same chemical environment of Ti (See XPS result) and similar TiCl 4 loading in the PS-modified and PS-free catalyst demonstrate the less interaction between PS chains and active species. Thus, this enhanced activity may be attributed to the isolated effect of the inert PS blocks, since the PS phase is thermally immiscible with the polyethylene and serves as the inert isolator for separate the propagated chains.…”
Section: Ethylene Polymerization Resultsmentioning
confidence: 86%
“…We have developed an improved phase inversion method to prepare polymer‐coated SiO 2 microspheres 27. These microspheres have been successfully used to support Ziegler–Natta or hybrid Ziegler–Natta/metallocene catalysts for production of polyethylene with broad or bimodal MWD 28, 29. Besides the role as the hybrid support, our results implied that the polymer affected the mass transfer of different reactants.…”
Section: Introductionmentioning
confidence: 77%
“…It was evidenced in our previous work that the PSA layers were compact with a nonporous structure . The immobilization of vanadium active sites depended on the swelling behaviors of PSA in n ‐hexane (in Cat‐2); this made the distribution of vanadium along the radial direction of PSA layer continuous . Thus, the synthesized polymer showed the numbers of thread structure with closest packing (see Figure S3, Supporting Information, for the particle morphology); this suggested that the PSA layer endowed a strong transfer resistance to the monomer during polymerization .…”
Section: Resultsmentioning
confidence: 99%
“…The activity of Cat‐2 only reached 2.3 × 10 5 g of PE/(mol [Fe] ·h) with the addition of MAO (run 3 in Table ). This low activity was attributed to the strong transfer resistance endowed by the outside PSA layer . Cat‐2 showed no catalytic activity with the presence of DEAC because the strong Lewis acid of DEAC could not activate the Fe active centers .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation